2020
DOI: 10.1108/bfj-07-2019-0490
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived stress on US millennials' external and emotional eating behavior

Abstract: PurposeThe purpose of this paper is to identify the relationship between Millennials' perceived stress and their external and emotional eating behaviors. Furthermore, the moderating effect of nutritional knowledge on the relationship between perceived stress and emotional eating and perceived stress and external eating of US Millennials was tested.Design/methodology/approachData was collected from 649 Millennials between the ages of 18 and 35 in the United States, and structural equation modeling (SEM) was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Another explanation could be that this behavior is a response to emotional states related to anxiety produced by home confinement [ 47 ]. Similarly, developing external eating behavior during isolation can be an external motivational response to stress, since this behavior occurs when individuals under stress are in the same environment with food, being affected by its smell and appearance [ 48 , 49 ]. Thus, it can be thought that the confinement at home and easy access to food has created a favorable environment for people eating more, especially those who previously were stigmatized for their body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that this behavior is a response to emotional states related to anxiety produced by home confinement [ 47 ]. Similarly, developing external eating behavior during isolation can be an external motivational response to stress, since this behavior occurs when individuals under stress are in the same environment with food, being affected by its smell and appearance [ 48 , 49 ]. Thus, it can be thought that the confinement at home and easy access to food has created a favorable environment for people eating more, especially those who previously were stigmatized for their body weight.…”
Section: Discussionmentioning
confidence: 99%
“…A generation analysis revealed that Generation Yers perform physical exercises to improve their health status, physical appearance, strength, endurance and managing their weight (Egli et al, 2011). Generation Yers are also more conscious of the advantages of wholesome food, healthy eating and wellness than other generations (Okumus and Ozturk, 2020). Recent industry surveys (i.e.…”
Section: Generation Y and Exercisementioning
confidence: 99%
“…Despite the prominence of Millennials in the US restaurant industry, little research has solely been conducted about their dining out behaviors. Existing studies on Millennials and their food and beverage consumption behaviors has focused on food trucks (Yoon and Chung, 2018), menu information preferences (Hammond et al, 2013), food choices and technology (Saulo, 2016;Okumus et al, 2018;Okumus and Ozturk, 2020), and cooking preferences (Namin et al, 2020). Against this backdrop, the current research specifically aims to study Gen Y's dining out preferences to comprehend changes in views over time and document technological, economic and social shifts across this generational cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that food intake functions to narrow down human's cognitive attention to immediate and pleasurable objectives (i.e., food), food craving under stressful circumstances is considered to be part of a fundamental aspect of human nature that seeks to reduce the consumer's psychophysiological burden(Okumus and Ozturk, 2021). 2 Food craving is defined as "an intense desire to consume a specific food" (Rodriguez-Martin and Meule, 2015, p. 1).…”
mentioning
confidence: 99%